2008
DOI: 10.1111/j.1471-4159.2008.05489.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale analysis of glucocorticoid target genes in rat hypothalamus

Abstract: Insufficient glucocorticoid (GC) signaling is frequently observed in major depressive disorder (MDD). Since emotional and behavioral symptoms are often accompanied by disturbances in hypothalamic systems, GC insufficiency in this region is regarded as important in the pathogenesis of MDD. In this study, 22 early GC‐responsive genes comprising 15 up‐regulated and 7 down‐regulated genes in rat hypothalamus were identified as being regulated at least two‐fold by dexamethasone using microarray with 22 599 unique t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 58 publications
3
25
1
1
Order By: Relevance
“…Possibly, the presence of particular GR cofactors are responsible for a cell-type specific response to GR activation (e.g., Grenier et al, 2006;see also below). Contrary to the previously described effect of GCs on other brain regions such as the hippocampus (Datson et al, 2011) or hypothalamus (Verkuyl et al, 2004;Sato et al, 2008), there are no data to date demonstrating the transcriptional effect of GR stimulation in striatal neurons. It has been reported that dexamethasone administration dose-dependently induces the death of selective subtypes of striatal neurons (enkephalin-positive neurons), as well as hippocampal and septal neurons (Haynes et al, 2001).…”
Section: Discussion the Gc-dependent Component Of Morphineinduced Sigcontrasting
confidence: 75%
See 1 more Smart Citation
“…Possibly, the presence of particular GR cofactors are responsible for a cell-type specific response to GR activation (e.g., Grenier et al, 2006;see also below). Contrary to the previously described effect of GCs on other brain regions such as the hippocampus (Datson et al, 2011) or hypothalamus (Verkuyl et al, 2004;Sato et al, 2008), there are no data to date demonstrating the transcriptional effect of GR stimulation in striatal neurons. It has been reported that dexamethasone administration dose-dependently induces the death of selective subtypes of striatal neurons (enkephalin-positive neurons), as well as hippocampal and septal neurons (Haynes et al, 2001).…”
Section: Discussion the Gc-dependent Component Of Morphineinduced Sigcontrasting
confidence: 75%
“…This gene was at the top of the list of genes regulated, both, by dexamethasone in cultured astrocytes and by morphine in the mouse striatum. Alterations in the level of Sgk1 transcript or protein have been previously observed in the CNS in various models of stress (Koya et al, 2005;Murata et al, 2005;Yuen et al, 2010), after exposure to dexamethasone (Sato et al, 2008;David et al, 2005;van Gemert et al, 2006), drugs of abuse (Piechota et al, 2010b) and antidepressants (Conti et al, 2007), as well as in animal models of memory formation (von Hertzen and Giese, 2005) and neurodegeneration (Iwata et al, 2004;Rangone et al, 2004;Schoenebeck et al, 2005). Our results show that GR-responsive isoforms of Sgk1 are confined to astrocytes.…”
Section: Regulation Of Sgk1 Expression In Neural Cellssupporting
confidence: 73%
“…PLEKHF1 was identified as one of 5 glucocorticoid responsive genes in rat hypothalamus (Sato et al, 2008). A deficiency in SLITRK6 was associated with delay in synaptogenesis that impacts vision and hearing in mice and humans (Tekin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Serum/glucocorticoid regulated kinase 1 ( Sgk1 ) and Tsc22d3 (Glucocorticoid-induced leucine zipper ( Gilz )) in the PFC, and Pro-opiomelanocortin ( Pomc) in the pituitary. Sgk1 is a widely expressed kinase that is regulated by glucocorticoids via a regulatory DNA element approximately 1 kb upstream of the transcriptional start site (TSS) (Webster et al., 1993a, Maiyar et al., 1997, Sato et al., 2008). SGK1 has been proposed to play a role in a wide range of functions, regulating both genomic and non-genomic actions and has been implicated in the regulation of many neuronal processes such as neuronal excitability, excitotoxicity, oligodendrocyte morphology, hippocampal plasticity and memory function (Tsai et al., 2002, Miyata et al., 2011, Lang et al., 2006, Lang et al., 2010).…”
Section: Introductionmentioning
confidence: 99%